Neik dil nojawan aur mukhtalif kahaniyan - Shahab, Skiekh (Children Publication Karachi, 2012)
This collection of stories likely revolves around the adventures and experiences of a kind-hearted young person. The tales may explore themes of friendship, compassion, courage, and the importance of doing good deeds. Readers can expect to encounter various situations that highlight the positive qualities of a noble character and the rewards that often come from being kind and selfless.